Maternal antibiotic exposure and fetal outcomes: Is there evidence for teratogenicity? - Altintas Aykan, Duygun; Ergun, Yusuf (Annals of Medical Research, 2021)
None
Keywords: Anti-bacterial Agents; Pregnancy; Teratology.